Purchase and redemption decisions of mutual fund investors and the role of fund families - Stephan Jank; Michael Wedow (University of Cologne, Centre for Financial Research (CFR), 2010)
This paper investigates the purchases and redemptions of a large cross-sectional sample of German equity funds. We find that investors punish bad performance by selling their shares, but also have a tendency to sell winners. Investors in large fund families show higher sales and redemption rates. Further family size also affects the flow-performance relationship: Investors in large families punish bad performance more. Last, we find that inner family rankings play an important part for redemptions, with investors strongly redeeming their shares from intra-family losers.
Keywords: G20; G23; 330; Mutual Funds; Fund Family; Flow-Performance Relationship; Investmentfonds; Institutioneller Anleger; Anlageverhalten; Portfolio-Management; Aktienfonds; Wertpapieranalyse; Schätzung; Deutschland